Effects of physicochemical properties of nanomaterials on their toxicity. Issue 7 (19th December 2014) - Li, Xiaoming; Liu, Wei; Sun, Lianwen; Aifantis, Katerina E.; Yu, Bo; Fan, Yubo; Feng, Qingling; Cui, Fuzhai; Watari, Fumio
Abstract: Due to their unique size and properties, nanomaterials have numerous applications, which range from electronics, cosmetics, household appliances, energy storage, and semiconductor devices, to medical products such as biological sensors, drug carriers, bioprobes, and implants. Many of the promising properties of nanomaterials arise from their large surface to volume ratio and, therefore, nanobiomaterials that are implantable have a large contact area with the human body. Before, therefore, we can fully exploit nanomaterials, in medicine and bioengineering; it is necessary to understand how they can affect the human body. As a step in this direction, this review paper provides a comprehensive summary of the effects that the physicochemical properties of commonly used nanobiomaterials have on their toxicity. Furthermore, the possible mechanisms of toxicity are described with the aim to provide guidance concerning the design of the nanobiomaterials with desirable properties. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103: 2499–2507, 2015.